2006
DOI: 10.1093/rpd/ncm195
|View full text |Cite
|
Sign up to set email alerts
|

On the reassessment of doses in TL-dosimetry by measuring the residual dose

Abstract: Second readouts and the photo-transferred thermoluminscence (PTTL) method are sometimes used to reassess high doses. When using the common LiF:Mg,Ti, if the second readout is performed by a regular readout cycle of 13.3 s, its efficiency is low and the estimations cannot be obtained with acceptable accuracy for low doses in the 10-100 mSv range. By applying the PTTL method, the efficiency is much higher, but a high background is also present, deteriorating the quality of the reassessment. A simple and efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…TL thermoluminescence (color figure online) 6 Relationship between the number of counts obtained from the glow curves after the second readout in the dose range from 100 to 1000 mGy, for an UV exposure of 2 h, 3 h and 4 h at 70 °C. Measurement uncertainties-standard error of the mean (SEM) Abraham et al in 2007 and other authors observed a high TL background signal after UV exposure (Abraham et al 2007(Abraham et al , 2008Budzanowski et al 2013;Bhasin et al 1987). They also emphasized that it is necessary to subtract the high background before re-evaluating the dose.…”
Section: Resultsmentioning
confidence: 96%
“…TL thermoluminescence (color figure online) 6 Relationship between the number of counts obtained from the glow curves after the second readout in the dose range from 100 to 1000 mGy, for an UV exposure of 2 h, 3 h and 4 h at 70 °C. Measurement uncertainties-standard error of the mean (SEM) Abraham et al in 2007 and other authors observed a high TL background signal after UV exposure (Abraham et al 2007(Abraham et al , 2008Budzanowski et al 2013;Bhasin et al 1987). They also emphasized that it is necessary to subtract the high background before re-evaluating the dose.…”
Section: Resultsmentioning
confidence: 96%
“…The PTTL behavior of TLD-100 has been investigated by various researchers for a long time [5,8,9,[11][12][13][14][15][16][17][18][19][20]. Initial studies performed with TLD-100 have shown that dose reassessment with PTTL is possible for doses higher than 10mGy [11].…”
Section: Introductionmentioning
confidence: 99%